Evaluation of MAIAC aerosol retrievals over China. (1st April 2019) - Zhang, Zhaoyang; Wu, Weiling; Fan, Meng; Wei, Jing; Tan, Yunhui; Wang, Quan
Abstract: Multiangle Implementation of Atmospheric Correction (MAIAC) is a new aerosol algorithm developed to retrieve aerosol optical depth (AOD) over land using the time series data to dynamically isolate aerosol and land contributions. However, there are still no comprehensive research on the quality of MAIAC AOD over China. In this paper, 1 km MAIAC AOD over China were examined against ground-based measurements to evaluate the performance of the data. In general, Aqua and Terra MAIAC retrievals have a high correlation coefficient (0.924 for Aqua and 0.933 for Terra) with ground-based observations and there are more than 72% of retrievals falling within the Expected Errors (EE = ±(0.05 + 0.2*AOD)). We found that the accuracy of MAIAC AOD is related with the AOD magnitude, aerosol size, seasons and surface types. In spring and summer, the AOD bias was influenced by both aerosol model and surface reflectance estimation. We also found that the aerosol model is the main source of AOD bias over desert regions. These results indicated that the MAIAC AOD could be used as a new aerosol data source for air quality and climate studies in China. Highlights: A comprehensive research was conducted to evaluate the performance of MAIAC aerosol products over China. The accuracy of MAIAC AOD is related with the AOD magnitude, aerosol size, seasons, and surface types. Good performance of Aqua and Terra MAIAC retrievals are shown. The MAIAC AOD bias is mainly influenced by aerosol model in desert regions.